IoT-Based Air Quality Monitoring in Electronics Engineering Study Program Laboratories and Workshops - Purba, Angelia M.; Napitu, Daniel H. S.; Pardede, Morlan; Siburian, Jhonson (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Comfortable laboratory and workshop rooms with good air quality are important factors in maximizing the learning process. The level of user density in laboratories and workshops used by D3 Telecommunication Engineering and D4 Telecommunication Network Engineering Technology This study aims to monitor air quality in the laboratories and workshops of the Electronics Engineering study program. This study uses a direct monitoring method by measuring O2 and CO2 levels, dust, and humidity in the laboratory and workshop rooms of the electronics engineering study program. From the results of the measurements that have been taken, it has been determined that the workshop room and the electronics laboratory room 2 do not meet the threshold limit value (NBA) for CO2 levels and temperature. The measured CO2 levels in the Electronics Engineering Study Workshop are 4,221 ppm–8,721 ppm and 3,965 ppm–7,296 ppm in the Electronics Engineering Study Laboratory. The highest temperature measured in the Electronics Engineering Laboratory Workshop is 34.20 °C and 32.80 °C in the Electronics Laboratory-2 room.